CARNIAN THECOSPIRIDAE (BRACHIOPODA) FROM SAN CASSIANO FORMATION (CORTINA D'AMPEZZO, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Taxa belonging to the genus Thecospira Zugmayer, present in the San Cassiano Formation near Cortina d'Ampezzo are reviewed.The muscle field of the brachial valve is advanced as a diagnostic character, for the reason that the external morphology is not always observable, and often only isolated brachial valves are found.The microstructure of the shell of these taxa is discussed. This is composed of a primary layer, a secondary layer, and in Thecospira tyrolensis (Loretz) and Necospira semseyi Bittner, a tertiary layer only in the muscle field. All the taxa are pseudopunctate with taleolae; in no case were punctae observed.The family Thecospiridae is ascribable to the Order Stropbomenida, in accord with several authors, especially Dagys (1974).
Keywords: Morphology; Microstructure; Systematic Paleontology; Brachiopoda; Strophomenida; Carnian; San Cassiano Formation; Eastern Dolomites (Italy).